Analysis of cohesive devices in greta thunberg’s speech - Situmorang, Sarnauli; Anggraeni, Diana; Sigalingging, Bob M (Trigin Institute, 2024)
Cohesive devices are essential for creating a well-structured text. They have multiple purposes and should be handled with clarity to avoid misunderstandings and maintain their comprehensibility. This study highlights cohesive devices in Greta Thunberg’s speech entitled Blah Blah Blah delivered at the Pre-COP26 Youth4Climate 2021 event, utilizing theories by Halliday and Hasan (1976), Scinto (1983), and Hartnett (1986). The research examines the types and functions of grammatical and lexical cohesion in Thunberg’s speech, as well as the cohesiveness degree in the speech text. Using a qualitative descriptive research design, the study discovers 55 sentences that comprise different coherent devices. The results showed grammatical cohesion (references, substitutions, and conjunctions) and lexical cohesion (repetitions, synonyms, superordinate, and collocations). The most common type of grammatical cohesion observed is personal reference, which serves to prevent redundancy and develop connections within the text. The primary kind of lexical cohesion identified is repetition, which serves to highlight key terms and ensure the continuity of the theme. The speech demonstrates a very high level of grammatical cohesiveness and medium level of lexical cohesiveness.